RETRACTED: Mesenchymal Stem/Stromal Cells as a Vehicle for Cytokine Delivery: An Emerging Approach for Tumor Immunotherapy - Razeghian, Ehsan; Margiana, Ria; Chupradit, Supat; Bokov, Dmitry O.; Abdelbasset, Walid Kamal; Marofi, Faroogh; Shariatzadeh, Siavash; Tosan, Foad; Jarahian, Mostafa (Frontiers in Medicine, 2021)
Pro-inflammatory cytokines can effectively be used for tumor immunotherapy, affecting every step of the tumor immunity cycle. Thereby, they can restore antigen priming, improve the effector immune cells frequencies in the tumor microenvironment (TME), and eventually strengthen their cytolytic function. A renewed interest in the anti-cancer competencies of cytokines has resulted in a substantial promotion in the number of trials to address the safety and efficacy of cytokine-based therapeutic options. However, low response rate along with the high toxicity associated with high-dose cytokine for reaching desired therapeutic outcomes negatively affect their clinical utility. Recently, mesenchymal stem/stromal cells (MSCs) due to their pronounced tropism to tumors and also lower immunogenicity have become a promising vehicle for cytokine delivery for human malignancies. MSCs-based delivery of the cytokine can lead to the more effective immune cell-induced anti-tumor response, and provide sustained release of target cytokines, as widely evidenced in a myriad of xenograft models. In the current review, we offer a summary of the novel trends in cytokine immunotherapy using MSCs as a potent and encouraging carrier for anti-tumor cytokines, focusing on the last two decades' animal reports.